2005
DOI: 10.1158/0008-5472.can-04-3462
|View full text |Cite
|
Sign up to set email alerts
|

Both Antiangiogenesis- and Angiogenesis-Independent Effects Are Responsible for Hepatocellular Carcinoma Growth Arrest by Tyrosine Kinase Inhibitor PTK787/ZK222584

Abstract: Vascular endothelial growth factor (VEGF) plays an important role in tumor angiogenesis of hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 38 publications
(45 reference statements)
1
60
0
5
Order By: Relevance
“…Consistent with this, preclinical evaluations suggest that the antitumor activity of sorafenib in HCC may be mediated by inhibition of angiogenesis (through inhibition of receptor tyrosine kinases), although direct effects on cell proliferation and survival cannot be excluded (Wilhelm et al, 2004;Liu et al, 2005). The promising preclinical activity of sorafenib has since been supported by clinical studies (Zhu, 2008).…”
Section: Therapeutic Targets In Hccmentioning
confidence: 86%
See 1 more Smart Citation
“…Consistent with this, preclinical evaluations suggest that the antitumor activity of sorafenib in HCC may be mediated by inhibition of angiogenesis (through inhibition of receptor tyrosine kinases), although direct effects on cell proliferation and survival cannot be excluded (Wilhelm et al, 2004;Liu et al, 2005). The promising preclinical activity of sorafenib has since been supported by clinical studies (Zhu, 2008).…”
Section: Therapeutic Targets In Hccmentioning
confidence: 86%
“…In a preclinical study, it significantly reduced tumor volume and microvessel density in an HCC xenograft model (Liu et al, 2005). It also inhibited tumor cell proliferation and induced apoptosis in a dose-dependent manner (Liu et al, 2005).…”
Section: Therapeutic Targets In Hccmentioning
confidence: 99%
“…Overexpression of VEGF has been documented in HCC [7] . A study has demonstrated that VEGF has an autocrine effect in stimulating cancer cell proliferation in HCC in addition to its angiogenic effect, further underscoring the importance of VEGF in HCC [19] . A strong VEGF expression was observed in the tissue of HCC and closely associated with tumor progression and metastasis [20] .…”
Section: Discussionmentioning
confidence: 98%
“…Based on our previous finding about the effects of PTK787 on human HCC cell lines (29) and study the study of Lee et al (41) showing that oral feeding of PTK787 at the dose of 50 mg/kg yielded 62.4 (F16.0) h Amol/L plasma exposure, we applied PTK787 at the concentration of Amol/L, to the tumor and endothelial cell lines, and found inhibitory effects on cell cycle progression and induction of cell apoptosis in both cell lines. We have also tested the effects of PTK787 on a human umbilical vascular endothelial cell and a mouse tumor-derived endothelial cell inhibited the motility of tumor cells through the membrane, and the suppression was further enhanced by the administration of PTK787.…”
Section: Discussionmentioning
confidence: 99%